Konseling Individual dalam Memotivasi Ibadah Shalat Jama’ah bagi Siswa MTs NU 02 Al- Ma’arif Boja Kendal - Agus Riyadi; Saerozi Saerozi (UIN Antasari Banjarmasin, 2022)
This article analysed the implementation of individual counseling in motivating students to pray and to analyze the implementation of individual counseling in motivating congregational prayers at school for class VIII students at MTs NU 02 Al-Ma'arif Boja in terms of the perspective of the objectives of Islamic guidance and counseling. This research is included in the type of qualitative descriptive research. Data collection techniques using interviews, observation and documentation studies. Data analysis includes data reduction, data presentation, conclusion drawing and verification. The research findings are (1) In carrying out individual counseling, MTs NU 02 Al-Ma'arif Boja surrenders entirely to the BK teacher. scolded, but the BK teacher called the student to be assistanced by being guided, given advice, and motivation (2) Several factors that influence the motivation for praying are associations with friends who are not good, families who do not set an example, an environment that is not conducive. (3) The implementation of individual counseling in motivating congregational prayers at school for class VIII students at MTs NU 02 Al-Ma'arif Boja in terms of the perspective of Islamic guidance and counseling goals, the implementation of individual counseling is following the general goals and specific goals of guidance and Islamic counseling. The general goal is to help individuals realize themselves as fully human beings to achieve happiness in life in this world and the hereafter. Specific goals are to help individuals overcome the problems they are facing, to help individuals to maintain and develop situations and conditions that are good or that have been good so that they remain good or become better so that they will not be a source of problems for themselves and others.